Design of real-time data analysis system for physical training based on data mining technology. Issue 1 (July 2021) - Hui, Deng; Jin, Wang
Abstract: In competitive sports, the most direct and effective way to improve athletes' competitive level is to strengthen training. At present, the training mode is still mainly based on coaches' experience and athletes' physical conditions, and lacks scientific and effective data information as the basis for planning. In this paper, the software is developed in the core construction of recessed Linux, the VIX bus technology is take advantage of gather sports data, and the data mining technology based on collective information characteristic extraction is designed. This paper uses big data mining method to mine the information of sports evaluation, pick up the autocorrelation characteristics of data information flow of sports training real-time data analysis system, constructs the association rule feature set combined with the prior knowledge of sports evaluation, and realizes the database construction of sports training real-time data analysis system by using the association rule feature extraction and big data information fusion processing technology. The simulation results show that the accuracy of sports assess decision-making information mining using the real-time data analysis system of sports training is high, and the dependability of the system is satisfied.